Penggunaan model pembelajaran contextual teaching and learning untuk meningkatkan hasil belajar siswa MIN 2 Sarolangun - Puryanto, Heri (ARKA INSTITUTE, 2022)
This research is motivated by the low learning outcomes of fourth grade science students at MIN 2 Sarolangun, with a class average of 67. This research is a class action research (PTK). Aiming to improve the learning outcomes of 4th grade science students of MIN 2 Sarolangun. The subjects of this study were 4th grade students of MIN 2 Sarolangun, totaling 25 heterogeneous people. The data used in this study are data on natural science learning outcomes. This study presents learning outcomes obtained from odd semester grades. The learning outcomes that occurred from before the PTK was held with an average of 67 with a poor category, while after class action research in cycle I with an average of 69 with a sufficient category and in cycle II with an average of 73 with a good category and in cycle III with an average of 75 with a good category. The results of this study prove that the application of the contextual teaching and learning (CTL) learning model can improve the science learning outcomes of 4th grade students of MIN 2 Sarolangun.